2011
DOI: 10.1111/j.1464-5491.2010.03136.x
|View full text |Cite
|
Sign up to set email alerts
|

The use of the EQ-5D preference-based health status measure in adults with Type 2 diabetes mellitus

Abstract: Evidence supported validity, reliability and responsiveness of the EQ-5D in Type 2 diabetes. EQ-5D index scores associated with Type 2 diabetes and various complications can be useful for modelling health outcomes in economic evaluations of health programmes for Type 2 diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
121
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(130 citation statements)
references
References 83 publications
6
121
3
Order By: Relevance
“…With regard to HRQOL, the average index score was 0.67, identical to the expected EQ-5D value among a general sample of adult patients with type 2 diabetes. 11 Few patients in our All bolded items are statistically significant at the p<.05 or greater level. Modmoderate; Sevsevere; Ex/VGexcellent/very good sample had problems with self-care activities, while most patients had problems with pain.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…With regard to HRQOL, the average index score was 0.67, identical to the expected EQ-5D value among a general sample of adult patients with type 2 diabetes. 11 Few patients in our All bolded items are statistically significant at the p<.05 or greater level. Modmoderate; Sevsevere; Ex/VGexcellent/very good sample had problems with self-care activities, while most patients had problems with pain.…”
Section: Resultsmentioning
confidence: 99%
“…The effect size of 0.06 points for total medical home score on HRQOL is more than half of the 0.10-point difference observed between patients with no complications and those with retinopathy, and is about one-third of the 0.18-point difference associated with diabetic peripheral neuropathic pain. 11 Thus, changes in the delivery of primary care may have clinically meaningful benefits to the quality of life of patients with diabetes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The National Institute for Clinical Excellence (NICE) recommends the EQ-5D as the preferred UK measure of health-related QoL in adults (National Institute for Health and Clinical Excellence, 2008), and its validity in assessing chronic illnesses is confirmed (Dyer, Goldsmith, Sharples, & Buxton, 2010;Janssen, Lubetkin, Sekhobo, & Pickard, 2011;Pickard et al, 2008).…”
Section: Health Status (Eq-5d)mentioning
confidence: 99%
“…Oga et al [11] and McTaggart-Cowan et al [13] reported a high ceiling effect (59% and 50% of the sample with the maximum score, respectively) questioning the usefulness of the EQ-5D in these patients. In fact, limitations related to the high ceiling effect have also been consistently reported for the EQ-5D in other chronic conditions, such as COPD [14], osteoarthritis [14], diabetes [15] and coronary heart disease [16].…”
Section: Introductionmentioning
confidence: 99%